Possibility of The Typical Sidewalks and Pedestrian Paths in The Urban Cities "Aqaba City as a Model - Dr. Mansour Mahmoud Alsalem Safran, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims at revealing the extent of possibility to employ the typical sidewalks and Pedestrian paths in Aqaba city- Jordan. The researcher used the descriptive and case study methods, referring to a number of resources like the photos and special data concerning the roads and streets in the city to find out extent of employing these sidewalks and pedestrian paths in order to guarantee safe and smooth movement in consistency with the general plan components, including pedestrian paths for these with special needs and cyclists to keep abreast with the urban development and reducing the traffic as much as possible. The study reached solutions regarding development and enhancing the functions of the sidewalks and pedestrian paths in the city to reduce accidents by applying the higher standards of quality in the design and the implementation